Right Vocal Cord Paralysis Caused by Histoplasmosis: A Case Report. (March 2023) - Diaz, Ashley; Auger, Samuel; Cipriani, Nicole A.; Baird, Brandon J.
Objectives: Histoplasma capsulatum is a prevalent dimorphic fungus, reaching an exposure rate of 90% in endemic areas such as the Midwest and Central United States. We report an unusual presentation of dysphonia due to right vocal cord paralysis caused by mediastinal lymphadenopathy from histoplasmosis. Methods: A 73-year-old male presented to an otolaryngology clinic with 4 months of hoarseness. Flexible strobolaryngoscopy demonstrated right vocal cord paralysis in lateral position and a full length glottic gap. Computerized tomography (CT) scan showed enlargement of a right paratracheal node. Results: A lymph node biopsy was obtained and showed histoplasmosis. He was treated with a 3-month course of pozaconazole. He then received a vocal cord medialization injection 2 months after symptom onset, which produced favorable improvement of his symptoms at 8-month follow up. Conclusions: One other case report in the literature has reported left vocal cord paralysis related to histoplasmosis. This first case of right vocal cord paralysis was extremely unusual and is not often included in the differential diagnosis of vocal cord paralysis.